IFAS Guidance for Huanglongbing (Greening) Management - Timothy M. Spann; Ryan A. Atwood; Megan M. Dewdney; Robert C. Ebel; Reza Ehsani; Gary England; Steve H. Futch; Tim Gaver; Tim Hurner; Chris Oswalt; Michael E. Rogers; Fritz M. Roka; et al. (EDIS)
HS1165, a 7-page fact sheet by Timothy M. Spann, Ryan A. Atwood, Megan M. Dewdney, Robert C. Ebel, Reza Ehsani, Gary England, Stephen H. Futch, Tim Gaver, Tim Hurner, Chris Oswalt, Michael E. Rogers, Fritz M. Roka, Mark A. Ritenour, Mongi Zekri, Brian J. Boman, Kuang-Ren Chung, Michelle D. Danyluk, Renee Goodrich-Schneider, Kelly T. Morgan, Robert A. Morris, Ronald P. Muraro, Pamela Roberts, Robert E. Rouse, Arnold W. Schumann, Philip A. Stansly, and Lukasz L. Stelinski, provides guidance to the Florida citrus industry in making management decisions regarding huanglongbing (HLB, citrus greening). Published by the UF Department of Horticultural Sciences, June 2010.